An Acute Ischemic Stroke After the Retrograde Transaortic Manipulation - Juan Xu; Shuang Wu; Xiaofeng Lu; Shi Peng; Jun Li; Shaowen Liu; Songwen Chen (Clinical Case Reports)
ABSTRACT Acute ischemic stroke (AIS) during radiofrequency ablation of premature ventricular complexes (PVC) patients was rarely reported. This is the first case report on AIS during catheter ablation of PVC that highlighted that AIS could be encountered in some patients resulting from repeated retrograde transaortic manipulation with excessive contact force.